STUDI PENERAPAN TEKNOLOGI SOLAR TUNNEL DRYING PADA PROSES PRODUKSI TIWUL INSTAN - Fifi Sutanto Darmadi; Kristina Ananingsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
Instant Tiwul, food made from dried cassava is one form of the modernisation of traditional food. With the liberalization of the global trade, and the fact that the consumers are more and more demanding on standardized processing and product, production for instant Tiwul with Open-Air Sun Drying can not perform to produce a quality product in general as well methodically. This research aimed at giving a real illustration of implementation of solar tunnel drying technology specifically for instant Tiwul processing. Effects of drying methods (Open-Air Sun Drying, Solar Tunnel Drying and Cabinet Drying) and pre drying treatment - hot water blanching to process- and product quality parameters were analysed in this research. The research result showed Solar Tunnel Drying had given a tendency the best process- and product quality parameters and remembering Solar Tunnel Drying as an environmental friendly technology, therefore its implementation for instant Tiwul production is recommended.